(untitled) (Estudios Gerenciales, 2015)
This paper aims to identify the differences and similarities in the way to explain self-organization from the different theories of complex systems used in management, which we have grouped as complex systems theories, complex adaptive systems (CAS) and organizational cybernetics. For this purpose we suggest three parallel and complementary dimensions to delimit the conceptual spaces where these theories can be placed. Using this classification as an analytical lens we summarize the core arguments suggested by each of these complex systems approaches, regarding the ideas of emergence and new order. This analysis helps us to conclude that the three theories coincide in their interest for studying nonlinear complex systems, but diverge in the nature of the complex problems studied. Finally we analyze the consequences that recognizing the similarities and differences between these approaches have, when using them for the study and research of social and business organizations and their management.